Effect of progesterone and/or estradiol treatments prior to induction of ovulation on subsequent luteal lifespan in anestrous Nelore cows - Sa Filho, Ocilon Gomes [UNESP]; Thatcher, William Watters; Vasconcelos, José Luiz Moraes [UNESP] (Elsevier B.V., 2009)
Three experiments evaluated effects of estradiol (E(2)) and/or progesterone (P(4)) prior to induction of ovulation with GnRH on subsequent luteal lifespan in anestrous Nelore cows. In Experiment 1, cows (25-65 days post-partum [DPP]; n = 114) were assigned randomly to receive a 6-day treatment with an intravaginal R device (CIDR(R)) and/or 1 mg i.m. injection of 17 beta-E(2) (4 groups; 2 x 2 factorial design) prior to ovulation. Blood samples were collected on days 0, 5, 7, 9, 12, 15 and 19 for evaluation of luteal function. Pre-treatment with P(4) reduced occurrence of premature luteolysis (PL; 79.2% in non-treated vs. 13.5% in treated cows; P < 0.01), but there was no effect of treatment with 17 beta-E(2) on percentage of PL. In Experiment 2, cows (30-40 DPP; n =: 35) were assigned randomly to receive either 0.5 mL i.m. injection of cottonseed oil (placebo) or 1 mg i.m. injection of E(2) cypionate. Blood samples were collected on days 0, 5, 9 and 15 for evaluation of luteal function. Incidence of PL (83.0% in Control Group vs. 75.0% in ECP Group; P>0.1) and mean serum P(4) did not differ between treatment groups. In Experiment 3, cows (30-60 DPP; it = 109) were randomly assigned to receive either a 6-day (6-d Group) or a 3-day (3-d Group) treatment with CIDR(R). Blood samples were collected on days 0, 5, 7 and 9 for luteal function evaluation. Incidence of PL (5.5% in 6-day vs. 5.5% in 3-day groups; P > 0.1) and mean serum P(4) did not differ between treatment groups. In conclusion, both 3- and 6-day treatments with P(4) prior to induction of ovulation in anestrous Nelore cows increased percentage of normal luteal lifespan, while administration of 1 mg of 17 beta-E(2) or E(2) cypionate failed to prevent occurrence of PL. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Cattle-anestrous; 17 beta-Estradiol; Estradiol cypionate; Progesterone; Short estrous cycle